2019
DOI: 10.1111/jfpp.14064
|View full text |Cite
|
Sign up to set email alerts
|

Compared extraction methods on the physicochemical properties, antioxidant activity, and optimization of enzyme‐assisted extraction of polysaccharides from Gynura medica

Abstract: The effects of hot water extraction (HWE), enzyme‐assisted extraction (EAE), ultrasonic‐assisted extraction (UAE), and ultrasonic‐enzyme‐assisted extraction (UEAE) methods on the extraction yield, physicochemical properties, and antioxidant activities of Gynura medica polysaccharides (GMPs) were investigated. The GMPs extracted by four methods were designated GMPs‐H, GMPs‐E, GMPs‐U, and GMPs‐UE, respectively. Meanwhile, the EAE method was further optimized by response surface methodology (RSM). The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…At high temperatures, some of the reducing sugars may react with amino acids present in plant materials to produce complex compounds, which may interact with polysaccharides and cause them to degrade and thus reduce the extraction yield. Generally, in HWE, a material‐to‐liquid ratio of about 1:20 is used to concentrate the extract, and thermal degradation of polysaccharides can occur 27 . Other disadvantages of this method are a long extraction time and a large volume of ethanol (4–10 times) required to precipitate crude polysaccharides.…”
Section: Extraction Methods For Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…At high temperatures, some of the reducing sugars may react with amino acids present in plant materials to produce complex compounds, which may interact with polysaccharides and cause them to degrade and thus reduce the extraction yield. Generally, in HWE, a material‐to‐liquid ratio of about 1:20 is used to concentrate the extract, and thermal degradation of polysaccharides can occur 27 . Other disadvantages of this method are a long extraction time and a large volume of ethanol (4–10 times) required to precipitate crude polysaccharides.…”
Section: Extraction Methods For Polysaccharidesmentioning
confidence: 99%
“…Generally, in HWE, a material-to-liquid ratio of about 1:20 is used to concentrate the extract, and thermal degradation of polysaccharides can occur. 27 Other disadvantages of this method are a long extraction time and a large volume of ethanol (4-10 times) required to precipitate crude polysaccharides. Previous studies suggested that HWE can only extract extracellular polysaccharides and cannot destroy the cell wall and plasma membrane of plant materials.…”
Section: Hot-water Extractionmentioning
confidence: 99%
“…Ultrasound-assisted extractions (UAEs) are applied for the isolation of many compounds such as flavonoids (Das et al, 2021;Valu et al, 2020), polysaccharides (Chen et al, 2020;Li et al, 2019), triterpenoids (Cheng et al, 2017), and alkaloids (Zuo et al, 2004)…”
Section: Several Green Alternatives For the Extraction Of Natural Pro...mentioning
confidence: 99%
“…Ultrasound‐assisted extractions (UAEs) are applied for the isolation of many compounds such as flavonoids (Das et al, 2021; Valu et al, 2020), polysaccharides (Chen et al, 2020; Li et al, 2019), triterpenoids (Cheng et al, 2017), and alkaloids (Zuo et al, 2004) from plant materials. Ultrasonic waves create intracellular cavities that disrupt plant cells and facilitate mass transfer by improving the velocity of solvent molecules.…”
Section: Introductionmentioning
confidence: 99%